Black belt negotiating : become a master negotiator using powerful lessons from the martial arts - Lee, Michael Soon (American Management Association, 2007)
This book uses the principles of martial arts to guide readers step-by-step, from basic techniques through advanced strategies, all the way to achieving their "black belt" in negotiating. Packed with quizzes, scripts, checklists, and even a Negotiating Rating Sheet for continual self-assessment, the book trains readers in martial arts-based negotiation fundamentals